Multi-omics signatures in new-onset diabetes predict metabolic response to dietary inulin: findings from an observational study followed by an interventional trial - Ďásková, Nikola; Modos, I.; Krbcová, M.; Kuzma, M.; Pelantová, H.; Hradecký, J.; Heczková, M.; Bratová, M.; Videňská, P.; Šplíchalová, P.; Králová, M.; Heniková, M.; et al. (Nutrition & Diabetes, 2023)
The metabolic performance of the gut microbiota contributes to the onset of type 2 diabetes. However, targeted dietary interventions are limited by the highly variable inter-individual response. We hypothesized (1) that the composition of the complex gut microbiome and metabolome (MIME) differ across metabolic spectra (lean-obese-diabetes); (2) that specific MIME patterns could explain the differential responses to dietary inulin; and (3) that the response can be predicted based on baseline MIME signature and clinical characteristics.
Gesehen am 15.06.2023